2012
DOI: 10.11002/kjfp.2012.19.4.604
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition and in vitro Antioxidant Activities of Blueberry (Vaccinium ashei) Leaf

Abstract: The nutritional composition and in vitro anti-oxidant activities of blueberry (Vaccinium ashei) leaf extract were investigated to examine their physiological characteristics. Calcium was the most abundant mineral. The principal free sugars were glucose, sucrose, maltose, and fructose. The amino acids were mainly composed of glutamic acid and aspartic acid. The fatty acids consisted mainly of 40.94% saturated fatty acid and 54.35% unsaturated fatty acid. In addition, the 112.64 mg% of vitamin C was analyzed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Blueberry ( Vaccinium ashei Reade; BB) containing anthocyanin had an antioxidant activity (Deng et al., ; Jeong, Jo, Jeong, Kim, & Heo, ; Vizzotto, da Rosa Fetter, Corbelini, Pereira, & Gonzales, ) and showed antioxidant effect on animals (Dunlap, Reynolds, & Duffy, ; Molan, Lila, & Mawson, ; Papandreou et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Blueberry ( Vaccinium ashei Reade; BB) containing anthocyanin had an antioxidant activity (Deng et al., ; Jeong, Jo, Jeong, Kim, & Heo, ; Vizzotto, da Rosa Fetter, Corbelini, Pereira, & Gonzales, ) and showed antioxidant effect on animals (Dunlap, Reynolds, & Duffy, ; Molan, Lila, & Mawson, ; Papandreou et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant properties have also been demonstrated for Southern black blueberry Vaccinium ashei Reade (BB) (anthocyanin; Jeong et al, 2012), persimmon Diospyros kaki L. (PM) (polyphenols; Hwang et al, 2011;Zhang et al, 2011), tomato Solanum lycopersicum L. (TT) (lycopene; Kim and Chin, 2011;Goyal et al, 2013), broccoli Brassica oleracea L. (BC) (gluconsinolates; Banerjee et al, 2012) and yacon Polymnia sonchifolia Poeppig and Endlicher (YC) (polyphenols; Kim et al, 2010a;Park et al, 2012). The effectiveness of oral application in animals was shown for all of these species (BB: Dunlap et al, 2006;Molan et al, 2008;Papandreou et al, 2009;PM: Kim et al, 2003;Chen et al, 2012;TT: Bobek, 1999;Moreira et al, 2005;BC: Muller et al, 2012;Tomofuji et al, 2012;YC: Kim, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…In addition, dietary supplementation of GG has been reported to ameliorate the non-specific immune responses and disease resistance to various pathogens in tilapia (Oreochromis mossambicus) and Asian seabass (Lates calcarifer) (Immanuel et al, 2009;. Blueberry (BB) (Vaccinium ashei Reade) is a perennial flowering plant with a high concentration of polyphenols, such as anthocyanins, flavonoids, and proanthocyanidins (Howard et al, 2003;Naczk et al, 2006), and also contains antioxidant (Jeong et al, 2012;Vizzotto et al, 2013), antimicrobial, anti-inflammatory, and neuroactive properties (Deng et al, 2014;Gurjar et al, 2012;Howard et al, 2003). Kim et al (2016) revealed that a diet supplemented with BB equally enhanced disease resistance against S. parauberis in rockfish as did YC and GG.…”
Section: Introductionmentioning
confidence: 99%